We are the world (but only at the end of the world): Race, disaster, and the Anthropocene. (February 2020) - Joo, Hee-Jung S
This essay explores the racial politics of a select group of contemporary disaster film and fiction to reveal the relationship between race and futurity that also undergirds discussions of the Anthropocene. I provide a comparative close reading of the disasters in Roland Emmerich's The Day After Tomorrow and 2012, Behn Zeitlin's Beasts of the Southern Wild, and Karen Tei Yamashita's Through the Arc of the Rain Forest . I argue that the cultural anxieties that structure these texts are expressions of the racial logic rooted in universalist concerns for the future of humanity, the very concern of the Anthropocene. Arguing against inclusion as the means of achieving equality and toward a new materialist understanding of race, my paper illuminates not only the racial assumptions of the Anthropocene but also, and perhaps more importantly, its racial consequences.